LIVING CONDITIONS AND HEALTH OF KAINGANG INDIGENOUS PEOPLE WITH DIABETES - Benedito, Júnior Cesar de Souza; Marcon, Sonia Silva; Medeiros, Arthur de Almeida; Batiston, Adriane Pires; Haddad, Maria do Carmo Lourenço; Teston, Elen Ferraz (Cogitare Enfermagem, 2024)
Objective: To analyze the living conditions and health of Kaingang indigenous people with type 2 Diabetes Mellitus. Method: A cross-sectional study carried out through interviews and consultation of medical records with indigenous people of the Kaingang ethnic group living in an indigenous land in the northern region of Paraná-Brazil. Student’s t-test and the chi-square test were used to analyze the data. Results: The average age of the 45 participants was 56.3 ± 12.4 years. Most women were overweight, and their waist circumference was higher than the risk indicator. The average glycated hemoglobin was 9.6 ± 2.7%, and venous glycemia was 189.1 ± 95.3 mg/dL. Conclusion: analyzing the living conditions and health of Kaingang indigenous people provides information for planning early screening, prevention, and monitoring of chronic conditions in the indigenous population.